2018
DOI: 10.3390/rs10020243
|View full text |Cite
|
Sign up to set email alerts
|

An Aircraft Detection Framework Based on Reinforcement Learning and Convolutional Neural Networks in Remote Sensing Images

Abstract: Aircraft detection has attracted increasing attention in the field of remote sensing image analysis. Complex background, illumination change and variations of aircraft kind and size in remote sensing images make the task challenging. In our work, we propose an effective aircraft detection framework based on reinforcement learning and a convolutional neural network (CNN) model. Aircraft in remote sensing images can be accurately and robustly located with the help of the searching mechanism that the candidate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Fu et al [122] have shown the feasibility of using deep reinforcement learning for remote sensing ship detection task. Recently, Li et al [123] have proposed an interesting aircraft detection framework based on the combination of a CNN model with reinforcement learning. Similarly, the change detection process can be solved as an action-decision problem based on a sequence of actions refining the size of the changed regions between two input images.…”
Section: A Deep Reinforcement Learningmentioning
confidence: 99%
“…Fu et al [122] have shown the feasibility of using deep reinforcement learning for remote sensing ship detection task. Recently, Li et al [123] have proposed an interesting aircraft detection framework based on the combination of a CNN model with reinforcement learning. Similarly, the change detection process can be solved as an action-decision problem based on a sequence of actions refining the size of the changed regions between two input images.…”
Section: A Deep Reinforcement Learningmentioning
confidence: 99%
“…The route planning problem is often addressed in RL, utilizing an RL algorithm that yields the maximum reward value for an unmanned ship. In aircraft detection systems and radar designs, RL is applied to optimal radar system design and aircraft image analysis to detect radio waves and minimize unnecessary interference [25][26][27].…”
Section: Learning From Demonstrationmentioning
confidence: 99%
“…The approach not only considered the complex spatial dependence of labels but also effectively learned the textural and spatial characteristics of images. Li 13 proposed a deep image detection and description framework by combining enhanced learning with a deep CNN to address the increased difficulty of aircraft identification in remote sensing images owing to a series of problems such as illumination and changes in aircraft type and size. The approach was demonstrated to accurately identify the specific positions of aircraft in remote sensing images.…”
Section: Introductionmentioning
confidence: 99%